THE EFFECTS OF ECONOMIC GROWTH, EDUCATION, AND GOVERNMENT EXPENDITURE ON POVERTY IN INDONESIA - Asawidya, Putri Ayu; Pratomo, Devanto Shasta (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
Poverty is one of the problems in the economy are complex and multidimensional. Therefore, it is necessary to find a solution to overcome the problem of poverty. The purpose of this study is conducted to see the effects of economic growth, education and government expenditure on the poverty in Indonesia. In this study was descriptive quantitative uses panel data. The data used is time series data (2007-2012 periods) and cross section data (33 provinces in Indonesia). Type of data uses secondary data as data which are processed by sources of data or related institutions such as Central Bureau of Statistics. Method of analysis used in this study is used linear regression panel data analysis (pooled data) with Random Effect Model as an instrument to process the data by using Stata 12 software applications. The finding shows that Economic Growth variable has not significant so economic growth variable will not influence significantly on the poverty variable. Education has a negative and significant influence on poverty variable. Government Expenditure has a negative and significant influence on poverty variable in Indonesia.Keywords: Poverty, Economic Growth, Education and Government Expenditure.